2020
DOI: 10.20944/preprints202002.0204.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Instant Controlled Pressure Drop (DIC) on Allergenic Potential of Tree Nuts

Abstract: Pistachio and cashew contain allergenic proteins, which causes them to be removed from the diet of allergic people. Former evidences have demonstrated that food processing (thermal and non-thermal) can produce structural and/or conformational changes in proteins by altering their allergenic capacity. In this study, the influence of Instant Controlled Pressure Drop (DIC) on the pistachio and cashew allergenic capacity has been studied. Western blot was carried out using IgG anti-11S and anti-2S and IgE antibodi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(58 reference statements)
3
6
0
Order By: Relevance
“…Other resolved pistachio protein bands Pi1/Pi2 may correspond to Pis v 1 (2S albumin, 7 and 17 kDa); Pi3 band for Pis v 4; Pi4, Pi6 and Pi7 to Pis v 2 subunits, a superoxide dismutase of 26 kDa and Pi8 band for Pis v3 [ 50 , 51 , 52 ]. In addition, the location and molecular weight of the SDS-PAGE-resolved pistachio bands agreed well with the pistachio allergen identifications by liquid chromatography-mass spectrometry (LC/MS/MS) recently reported by Vicente et al [ 53 ]. Moreover, the SDS-PAGE analysis of the prepared extracts showed that the utilization of optimal nondenaturing protein extraction conditions that are specific to peanut and to each selected tree nut [ 23 ] allows for a representative extraction of allergens, thereby facilitating a comprehensive investigation of sIgE-binding to a majority of peanut, almond, hazelnut and pistachio allergens.…”
Section: Resultssupporting
confidence: 88%
“…Other resolved pistachio protein bands Pi1/Pi2 may correspond to Pis v 1 (2S albumin, 7 and 17 kDa); Pi3 band for Pis v 4; Pi4, Pi6 and Pi7 to Pis v 2 subunits, a superoxide dismutase of 26 kDa and Pi8 band for Pis v3 [ 50 , 51 , 52 ]. In addition, the location and molecular weight of the SDS-PAGE-resolved pistachio bands agreed well with the pistachio allergen identifications by liquid chromatography-mass spectrometry (LC/MS/MS) recently reported by Vicente et al [ 53 ]. Moreover, the SDS-PAGE analysis of the prepared extracts showed that the utilization of optimal nondenaturing protein extraction conditions that are specific to peanut and to each selected tree nut [ 23 ] allows for a representative extraction of allergens, thereby facilitating a comprehensive investigation of sIgE-binding to a majority of peanut, almond, hazelnut and pistachio allergens.…”
Section: Resultssupporting
confidence: 88%
“…This tested Real-Time PCR assay, especially in the case of cashew, allowed the authors to potentially detect traces of the nuts treated by heat and pressure at 7 bar and 2 min, which resulted in the appearance of an immunoreactive response in sensitive patients. In that study [ 26 ], pistachio proteins were also more susceptible to DIC processing than cashew ones, and, according to our results, it was possible to detect and quantify treated cashew with good efficiency, much better than pistachio ( Figure S3 ).…”
Section: Resultssupporting
confidence: 67%
“…As mentioned with pistachio, Vicente and collaborators [ 26 ] showed, for the first time, by mass spectrometry, that major cashew allergens (Ana o 2 and Ana o 3) survived to DIC 7b 120 s processing, and triggered IgE immunoreactivity in patients, although a reduction in the capacity to bind IgE was noticeable. This tested Real-Time PCR assay, especially in the case of cashew, allowed the authors to potentially detect traces of the nuts treated by heat and pressure at 7 bar and 2 min, which resulted in the appearance of an immunoreactive response in sensitive patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations